KOMPETENSI, BUDAYA ORGANISASI DAN KINERJA PEGAWAI - Asparida, Zaili Rusli, Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Competence, Organizational Culture and Employee Performance. This researchuses a descriptive quantitative research method approach. The purpose of this study is to determinethe competence, organizational culture and employee performance. Direct data collectiontechniques through questionnaires to the State civil apparatus in the District of Rumbai, amountingto 56 people and secondary data obtained from the district of Rumbai. Data analysis uses productmoment regression correlation. The results showed that the performance variable of the employeesof the Rumbai district of Pekanbaru in the good category, from the four performance indicators itcould be seen that the highest indicator was the quantity and cooperation built by the employees inworking for the community. Based on the results of the analysis it can be seen that the influence oforganizational competence and culture on the performance of the employees of the Rumbai districtof Pekanbaru City simultaneously has a significant effect and partially also has a significant effect,which can be seen that the influence of organizational culture is greater when compared toemployee competency.